PENGEMBANGAN WEBSITE PROFIL NANO HEALTHY FAMILY - Lina; Pragantha, Jeanny; Wasino; Rusdi, Zyad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ABSTRACT Nano Healthy Family is a business operating in the service sector that provides various traditional health treatments such as reflexology, massage and nail art. Nano Healthy Family has been established since 2005 and already has several branches in various areas in Jakarta and Tangerang. Nano Healthy Family is known for its traditional characteristics in every treatment service it provides. Even though the business carried out by Nano Healthy Family has developed rapidly, this business still experiences the lack of digital marketing models and relies only on conventional methods such as customers coming directly to the business locations or using only social media. Nano Healthy Family also does not have a website to display the professional side of the business. Therefore, to overcome this problem, the Community Service (PKM) team proposed developing a profile website for Nano Healthy Family as a forum for customers to search for information about various types of treatments, detailed benefits of each type of treatment, the prices of the available treatments, opening hours, and locations of Nano Healthy Family. The website development process started with interviewing the Nano Healthy Family owner and staffs, collecting historical data on Nano Healthy Family business along with its related photos, and taking pictures of the service rooms. Moreover, the PKM team analyzed the business needs, developed the website, and tested the website with the staffs. Furthermore, the website maintenance process will be carried out in the form of knowledge transfer activities from the PKM team to the partner team including handing over the website source code, the website administrator accounts, as well as trainings on how to use the website to staffs appointed by the partner team. ABSTRAK Nano Healthy Family merupakan sebuah usaha yang bergerak di bidang jasa yang menyediakan berbagai layanan kesehatan tradisional seperti reflexology, massage, maupun nail art. Nano Healthy Family sudah berdiri sejak tahun 2005 dan sudah memiliki beberapa cabang di berbagai daerah di Jakarta dan Tangerang. Nano Healthy Family ini dikenal akan ciri khasnya yang masih tradisional dalam setiap jasa treatment yang dilakukannya. Walaupun usaha yang dilakukan oleh Nano Healthy Family telah berkembang dengan pesat, namun permasalahan yang masih dialami bisnis ini adalah keterbatasan dari unit usaha untuk melakukan pemasaran yang hingga saat ini masih mengandalkan cara konvensional seperti pelanggan yang datang langsung ke lokasi usaha, maupun menggunakan media sosial saja. Nano Healthy Family juga tidak memiliki website untuk menampilkan sisi profesional bisnis yang mereka jalankan. Oleh karena itu, untuk mengatasi permasalahan ini, tim pelaksana Pengabdian Kepada Masyarakat (PKM) mengusulkan pengembangan website profil untuk Nano Healthy Family sebagai wadah untuk customer dalam mencari informasi seputar jenis layanan, manfaat detil dari setiap jenis layanan, harga, jam buka, lokasi dari Nano Healthy Family. Konsep pengembangan website akan dimulai dengan wawancara kebutuhan mitra, pengumpulan data sejarah Nano Healthy Family beserta foto terkait, dokumentasi terkait ruangan layanan, analisis terhadap kebutuhan website profil yang diinginkan mitra, pembuatan website, pengujian website oleh mitra, hingga akhirnya implementasi website oleh tim pelaksana PKM. Selanjutnya, untuk proses pemeliharaan website akan dilakukan dalam bentuk kegiatan knowledge transfer dari tim pelaksana PKM ke tim mitra meliputi penyerahan source code website, akun administrator website, serta pelatihan penggunaan website kepada staf yang ditunjuk oleh tim mitra.